Advancements in nanofibers for wound dressing: A review - Ambekar, Rushikesh S.; Kandasubramanian, Balasubramanian (European polymer journal, 2019)
[Display omitted] •Consolidated data on wound healing and wound dressing along with drug delivery mechanism.•The comprehensive wound healing process have been explained.•The therapeutic approach for reducing the healing time with nano/micro-fibers based wound dressing.•Classification of Electrospun nanofibers and their effect on the drug delivery efficiency. Chronic wound healing is an intricate time-consuming process (healing time ∼12 weeks), susceptible to external biological attack such as bacteria (e.g. E. coli, B. subtilis, S. aureus etc.) promoting wound infection and exhibit a negative effect on the immune system, therefore, it is a necessity to form a controlled environment for wound healing with the help of suitable barrier. Over the past few decades, various topical formulations of wound barriers like films, hydrogels, emulsions and nano/micro-fibers have been explored. The drug-embedded fibers are the potential candidate for wound healing as a barrier owing to the large specific surface area (for surface functionalization), enormous porosity ∼60–90% (for oxy-permeability), reticulated nano-porosity (for inhibition of the microorganism) and advanced electrospinning methodology which facilitates sustained drug release. Wound bed exhibits 37 °C temperature and 7.4 pH (typically for blood) condition which triggers the drug release and nano/micro-fiber degradation simultaneously. Drug-embedded nano/micro-fiber consists of a matrix with excellent biocompatibility, appreciable biodegradation rate (e.g. Chitin nanofiber-20% degradation in 15 days) and a drug with a superior antibiotic, antimicrobial property, besides certain drug (e.g. Captopril) also promote vasodilation which increases in-vascular permeability leading to rapid movement of leukocytes into the affected tissue, thereby reducing the healing time. In this review article, we discuss the consolidated recent advanced works on wound healing and wound dressing which implies the significance of wound dressing. In addition, the recent advancements in nano/micro-fiber fabrication methodology for drug release mechanism, and benefits of the fiber-based wound dressings compared to conventional wound dressings have been extensively discussed.